Аssessment of the effectiveness of antibacterial treatment of the root canal with a 3% solution of sodium hypochlorite with ultrasound treatment of chronic apical periodontitis (LLC "Endo Press", 2020)
Chronic apical periodontitis ranks third in terms of referral to a dentist. The main role in the development of this disease is attributed to the microbial factor. Therefore, in the treatment of chronic apical periodontitis, a qualitative antibacterial treatment of the root canal is necessary. Ultrasound is one of the methods of disinfection. With the help of clinical research, as well as microbiological examination of the microflora of the root canals of the teeth before and after antibacterial treatment, the anti-inflammatory and antimicrobial effect of ultrasound was assessed.